PENERAPAN TEKNIK GROUP CLOSE DALAM MEMBACA PEMAHAMAN SISWA KELAS VIII SMP PEMBANGUNAN UNP PADANG - Dwi Mutia Chan (Ta'dib, 2016)
AbstractThis reseach was motivated by low of students’ reading comprehension and their reading interest. To anticipate this problem, the researcher offered group close technique – a technique focussed to enrich students’ vocabulary the research used desciptive quantitative. The population of this research was the eight grade students of Junior High School (SMP) Pembangunan UNP Padang. The reseach sample were taken using random sampling. The instrument used was reading comprehension test. The research revealed students’ abililty as follows: (1) an excellent reader was 2.8 percent; (2) very good readers were 11.1 percent; (3) good readers were 11.1 percent; (4) adequate readers were 19.4 percent; (5) less adequate readers were 41.7 percent; and (6) poor readers were 22.2 percent.  Kata Kunci: penerapan, teknik group close, membaca pemahaman